Trade union participation in CSR deliberation: an evaluation. Issue 1 (January 2017) - Harvey, Geraint; Hodder, Andy; Brammer, Stephen
Abstract: Whereas there has been considerable interest in the concept of political corporate social responsibility (CSR), trade unions have been largely omitted from such scholarly discussion. This article explores the potential of trade unions as the other in political CSR and the contribution of trade unions to deliberative democracy with the firm. We discuss the importance both of the legitimacy and the efficacy of the other in political CSR. We proceed to assess trade unions as legitimate and effective deliberative partners with the firm towards CSR, evaluating the contribution of trade unions to deliberative democracy and also the potential outcomes for trade unions in adopting this role.